Music preferences in an asian culture: a cross-cultural extension of the music model - Leong, Li An (2017)
Music is present in many situations and used for various functions. Despite its usefulness, there is limited research into music preferences. Early research using music genres had methodological disagreements, prompting research to shift towards music dimensions. Rentfrow et al. (2011) proposed a five-factor model, termed the MUSIC model, to categorize music preferences based on music properties instead of genres. This model was further validated with music excerpts that were not commercially released and excerpts from single genres (Rentfrow et al., 2012). While these studies documented the robustness of the five-factor model, there is a lack of research extending this finding to other cultures. While existing literature suggested differences in music preferences due to culture differences, previous music preference research was mostly conducted using Western populations in Western contexts. To address this gap, the current study applied this MUSIC model to a non-Western population and examined its validity. Eighty-three university students were recruited and rated musical excerpts from the original Rentfrow study. Factor analyses did not yield a similar five-factor model, but a three-factor model with some dimensions that corresponded to the original MUSIC model. This suggested that the underlying structure of music preferences might be different in a non-Western culture. Discussion of the significance and implications for a potential culturally specific music preference model is presented. Future investigations in more homogenous non- western cultures can aid in prediction and linkage of personality traits, cognitive styles or behaviour that is unique to that culture.